Functionalization of 4-bromobenzo[c][2,7]naphthyridine via regioselective direct ring metalation. A novel approach to analogues of pyridoacridine alkaloids - Melzer, Benedikt C.; Plodek, Alois; Bracher, Franz (Beilstein Journal of Organic Chemistry, 2019)
Readily available 4-bromobenzo[c][2,7]naphthyridine undergoes regioselective direct ring metalation at C-5 with TMPMgCl∙LiCl at −40 °C. Quenching with various electrophiles gives a broad range of 5-substituted products, which are building blocks for the synthesis of heterocyclic natural products and analogues thereof. In combination with a Parham-type cyclization a novel approach to pyrido[4,3,2-mn]acridones has been worked out.
Keywords: alkaloids; cyclization; metalation; naphthyridine; pyridoacridine

(untitled) - Delfourne, E.; Bastide, J. (Med. Res. Rev., 2003)

(untitled) - Sandjo, L. P.; Kuete, V.; Biavatti, M. W. (Beilstein J. Org. Chem., 2015)

(untitled) - Plodek, A.; Bracher, F. (Mar. Drugs, 2016)

(untitled) - Joule, J. A.; Álvarez, M. (Eur. J. Org. Chem., 2019)

Chemistry and Biology, The Alkaloids - Lúcio, A. S. S. C.; Almeida, J. R. G. d. S.; da-Cunha, E. V. L.; Tavares, J. F.; Barbosa Filho, J. M. (Alkaloids of the Annonaceae: Occurrence and a Compilation of Their Biological Activities, 2015)

(untitled) - Skyler, D.; Heathcock, C. H. (J. Nat. Prod., 2002)

(untitled) - Bracher, F. (Arch. Pharm. (Weinheim, Ger.), 1989)

(untitled) - Lotter, M.; Bracher, F. (Sci. Pharm., 2009)

(untitled) - Godard, A.; Rocca, P.; Guillier, F.; Duvey, G.; Nivoliers, F.; Marsais, F.; Quéguiner, G. (Can. J. Chem., 2001)

(untitled) - Duvey, G.; Nivoliers, F.; Rocca, P.; Godard, A.; Marsais, F.; Quéguiner, G. (J. Heterocycl. Chem., 2001)

(untitled) - Guillier, F.; Nivoliers, F.; Godard, A.; Marsais, F.; Queguiner, G.; Siddiqui, M. A.; Snieckus, V. (J. Org. Chem., 1995)

(untitled) - Guillier, F.; Nivoliers, F.; Godard, A.; Marsais, F.; Quéguiner, G. (J. Heterocycl. Chem., 1999)

(untitled) - Cochennec, C.; Rocca, P.; Marsais, F.; Godard, A.; Quéguiner, G. (J. Chem. Soc., Perkin Trans. 1, 1995)

(untitled) - Plodek, A.; Raeder, S.; Bracher, F. (Tetrahedron, 2012)

(untitled) - Raeder, S.; Bracher, F. (Arch. Pharm. (Weinheim, Ger.), 2012)

(untitled) - Plodek, A.; Raeder, S.; Bracher, F. (Tetrahedron, 2013)

(untitled) - Plodek, A.; König, M.; Bracher, F. (Eur. J. Org. Chem., 2015)

(untitled) - Melzer, B.; Plodek, A.; Bracher, F. (J. Org. Chem., 2014)

(untitled) - Krasovskiy, A.; Krasovskaya, V.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Balkenhohl, M.; Knochel, P. (SynOpen, 2018)

(untitled) - Melzer, B.; Bracher, F. (Org. Biomol. Chem., 2015)

(untitled) - Melzer, B. C.; Bracher, F. (Beilstein J. Org. Chem., 2017)

(untitled) - Melzer, B. C.; Felber, J. G.; Bracher, F. (Beilstein J. Org. Chem., 2018)

(untitled) - Schnürch, M.; Spina, M.; Khan, A. F.; Mihovilovic, M. D.; Stanetty, P. (Chem. Soc. Rev., 2007)

(untitled) - Weymeels, E.; Awad, H.; Bischoff, L.; Mongin, F.; Trécourt, F.; Quéguiner, G.; Marsais, F. (Tetrahedron, 2005)

(untitled) - Greiner, R.; Ziegler, D. S.; Cibu, D.; Jakowetz, A. C.; Auras, F.; Bein, T.; Knochel, P. (Org. Lett., 2017)

(untitled) - Marquise, N.; Harford, P. J.; Chevallier, F.; Roisnel, T.; Wheatley, A. E. H.; Gros, P. C.; Mongin, F. (Tetrahedron Lett., 2013)

(untitled) - Chuang, T.-H.; Li, C.-F.; Lee, H.-Z.; Wen, Y.-C. (J. Org. Chem., 2013)

(untitled) - Dobbs, A. P.; Jones, K.; Veal, K. T. (Tetrahedron Lett., 1997)

(untitled) - Harayama, T.; Akiyama, T.; Akamatsu, H.; Kawano, K.; Abe, H.; Takeuchi, Y. (Synthesis, 2001)

(untitled) - Markgraf, J. H.; Dowst, A. A.; Hensley, L. A.; Jakobsche, C. E.; Kaltner, C. J.; Webb, P. J.; Zimmerman, P. W. (Tetrahedron, 2005)

(untitled) - Olivera, R.; SanMartin, R.; Tellitu, I.; Domı́nguez, E. (Tetrahedron, 2002)

(untitled) - Parham, W. E.; Bradsher, C. K. (Acc. Chem. Res., 1982)

(untitled) - Kristensen, J. L.; Vedsø, P.; Begtrup, M. (J. Org. Chem., 2003)

(untitled) - Krasovskiy, A.; Knochel, P. (Angew. Chem., Int. Ed., 2004)